Visible Spectrophotometric Determination of Apraclonidine in Dosage Form - Gandhimathi, M.; Ravi, T.K. (Asian Journal of Chemistry, 2010)
Two simple colorimetric methods for the estimation of apraclonidine in dosage from were developed. In method A apraclonidine undergoes reaction with p-dimethylaminobenzaldehyde in acidic medium to form chromogen with λmax at 450 nm and obeyed Beer's law in the concentration range of 4-24 μg/mL. In the method B based on the formation of diazotized coupling reaction with sodium nitrite, hydrochloric acid and chromotropic acid. The orangish chromogen had 529 nm as λmax with apparent molar absorptivity. The proposed methods gave precise and reproducible results for the estimation of apraclonidine from its dosage form.